MiR‐195 reduces age‐related blood–brain barrier leakage caused by thrombospondin‐1‐mediated selective autophagy. Issue 11 (7th October 2020) - Chen, Chien‐Yuan; Chao, Yung‐Mei; Lin, Hsiu‐Fen; Chen, Chao‐Jung; Chen, Cheng‐Sheng; Yang, Jenq‐Lin; Chan, Julie Y. H.; Juo, Suh‐Hang H.
Abstract: Blood–brain barrier (BBB) disruption contributes to neurodegenerative diseases. Loss of tight junction (TJ) proteins in cerebral endothelial cells (ECs) is a leading cause of BBB breakdown. We recently reported that miR‐195 provides vasoprotection, which urges us to explore the role of miR‐195 in BBB integrity. Here, we found cerebral miR‐195 levels decreased with age, and BBB leakage was significantly increased in miR‐195 knockout mice. Furthermore, exosomes from miR‐195‐enriched astrocytes increased endothelial TJ proteins and improved BBB integrity. To decipher how miR‐195 promoted BBB integrity, we first demonstrated that TJ proteins were metabolized via autophagic–lysosomal pathway and the autophagic adaptor p62 was necessary to promote TJ protein degradation in cerebral ECs. Next, proteomic analysis of exosomes revealed miR‐195‐suppressed thrombospondin‐1 (TSP1) as a major contributor to BBB disruption. Moreover, TSP1 was demonstrated to activate selective autophagy of TJ proteins by increasing the formation of claudin‐5‐p62 and ZO1‐p62 complexes in cerebral ECs while TSP1 impaired general autophagy. Delivering TSP1 antibody into the circulation showed dose‐dependent reduction of BBB leakage by 20%–40% in 25‐month‐old mice. Intravenous or intracerebroventricular injection of miR‐195 rescued TSP1‐induced BBB leakage. Dementia patients with BBB damage had higher levels of serum TSP1 compared to those without BBB damage ( p  = 0.0015), while the normal subjects had the lowest TSP1 ( p  < 0.0001). Taken together, the study implies that TSP1‐regulated selective autophagy facilitates the degradation of TJ proteins and weakens BBB integrity. An adequate level of miR‐195 can suppress the autophagy–lysosome pathway via a reduction of TSP1, which may be important for maintaining BBB function. Abstract : The present study revealed that thrombospondin‐1 (TSP1) is a key factor for BBB leakage and miR‐195 protects BBB integrity. We showed that cerebral miR‐195 reduces with age and blood‐brain barrier (BBB) leakage is increased in miR‐195 knockout mice. miR‐195‐regulated thrombospondin‐1 impairs BBB via selective autophagy of tight junctions. Furthermore, circulating TSP1 was higher in BBB‐damaged patients, which implied TSP1 as a new biomarker of BBB damage.